STUDIES ON THE INTERACTION BETWEEN TRIPTOLIDE AND BOVINE SERUM ALBUMIN (BSA) BY SPECTROSCOPIC AND MOLECULAR MODELING METHODS - Wang, Haidong; Shi, Hailang; Pang, Jie; Song, Xingfa; Xu, Caiyun; Sun, Zengxian (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Triptolide is a major active constituent isolated from Tripterygiumwilfordii Hook F, a Chinese herbal medicine. This study investigated the intermolecular interaction between triptolide and bovine serum albumin (BSA). Materials and Methods: The fluorescence, circular dichroism (CD) and molecular docking methods were used to investigate the intermolecular interaction between triptolide and BSA. The binding constant, the number of binding sites, binding subdomain and the thermodynamic parameters were measured. Results: The results of this experiment revealed that the intrinsic fluorescence of BSA was effectively quenched by triptolide via static quenching. The experimental results of synchronous fluorescence and CD spectra showed that the conformation of BSA was changed in the presence of triptolide. Conclusion: It indicated that triptolide could spontaneously bind on site II (subdomain IIIA) of BSA mainly via hydrogen bonding interactions and Van der Waals force.